Classified : the secret career of Mary Golda Ross, Cherokee aerospace engineer - Sorell, Traci (Millbrook Press, 2021)
"Mary Golda Ross designed classified projects for Lockheed Aircraft Corporation as the company's first female engineer. Find out how her passion for math and the Cherokee values she was raised with shaped her life and work"--